Perlindungan Hukum Bagi Korban Tindak Pidana Penipuan Pada Media Sosial - Yuni Yuni Kristania Purba; Roida Roida Nababan (Cattleya Darmaya Fortuna, 2025)
The rapid advancement of information technology has profoundly influenced many aspects of human life, including the dynamics of crime. Among the various types of offenses, one of the most common is classified as white-collar crime, typically committed by individuals who possess the knowledge and technical capability to exploit digital systems. The techniques employed are increasingly complex and varied, such as the use of false identities or the creation of deceptive social media accounts to manipulate and mislead potential victims. Consequently, a growing number of individuals suffer both material and non-material losses. A major issue that arises concerns the difficulty victims face in obtaining adequate legal protection. This challenge stems from inconsistencies in legal interpretation between the Criminal Code (KUHP) and Law Number 1 of 2024, which amends Law Number 11 of 2008 on Electronic Information and Transactions (ITE Law). The KUHP primarily emphasizes the criminalization of perpetrators and the elements of the offense, whereas the ITE Law provides a broader framework for victim protection and the restoration of victims’ rights, including compensation. This study aims to analyze the legal protection afforded to victims of fraud on social media and to examine the forms of cyber fraud that occur through these platforms. The research adopts a normative juridical approach, utilizing statutory, conceptual, and historical methods. The findings reveal that legal protection for victims of online fraud is formally provided under several legal instruments, including the Criminal Code, the Criminal Procedure Code, the Law on the Protection of Witnesses and Victims, and Law Number 1 of 2024 on Electronic Information and Transactions. However, implementation remains ineffective, hindered by weak law enforcement and low public digital literacy. Moreover, the forms of social media fraud continue to evolve, encompassing schemes such as online marketplace scams, fake job postings, and phishing activities. Although Article 378 of the Criminal Code still serves as the legal basis for prosecuting fraud, the application of the ITE Law as lex specialis is deemed necessary to effectively address and sanction perpetrators of digital crimes.